Tilings of the plane, hyperbolic groups, and small cancellation conditions - Krajčevski, Milé, 1954- (Memoirs of the American Mathematical Society, 2001)
Preface Acknowledgments Introduction Small cancellation theory of $\mathcal{T}$ Tilings Bibliography.